2000
DOI: 10.1002/1097-0134(20010101)42:1<6::aid-prot20>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the third loop of short-chain snake venom neurotoxins: Roles of the short-range and long-range interactions

Abstract: The influence of long-range interactions on local structures is an important issue in understanding protein folding process and protein structure stability. Using short-chain snake venom neurotoxin as a model system, we have studied the conformational properties of eight different loop III sequences either in the environment of one of the short-chain neurotoxin, erabutoxin b (PDB ID 1nxb), or in free state by Monte Carlo simulated annealing method. The surrounding protein structure was found to be crucial in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…The α-δ-Bgt-4 is a potent neurotoxin produced by highly venomous species from the Elapidae family of serpents, causes death without showing any local symptoms becoming the main cause for death of the bite victims [ [36] , [37] , [38] ]. The mechanism of resistance to snake toxins have also been studied through molecular modeling and structural analysis [ [39] , [40] , [41] ]. It has been also reported that a 13-mer peptide binds alpha-bungarotoxin with high affinity and neutralizes its toxicity [ [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…The α-δ-Bgt-4 is a potent neurotoxin produced by highly venomous species from the Elapidae family of serpents, causes death without showing any local symptoms becoming the main cause for death of the bite victims [ [36] , [37] , [38] ]. The mechanism of resistance to snake toxins have also been studied through molecular modeling and structural analysis [ [39] , [40] , [41] ]. It has been also reported that a 13-mer peptide binds alpha-bungarotoxin with high affinity and neutralizes its toxicity [ [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%